Errors Analysis: Students’ Pronunciation Assessment through IPA Application - Idayani, Andi; Estika Satriani; Via Elmanisa; Betty Sailun (ELT-Lectura, 2024)
Pronunciation is one of the most crucial subskills of English speaking. This study aims to determine students' pronunciation errors when pronouncing English short vowels in the fifth semester of English Language Education using the English Pronunciation IPA application and to determine the factors that influence their pronunciation errors. In this study, the researcher used a qualitative method design. It was conducted on students in fifth semester of English Language Education. The researcher collected data with two tools: pronunciation tests and interviews. Students can use the English Pronunciation IPA application as a help for taking long vowel pronunciation examinations. The researcher selected five students to serve as resource people for interviews. Based on the study results, the English Pronunciation IPA application was used to administer a pronunciation test to students. The results showed that, on average, students scored 15.57, with short vowels scoring 3.70 points. Pronouncing short vowels on the /ɒ/ and /æ/ sound are where students make the greatest mistakes. Then, interference and phonological knowledge are the factors that affect pupils' pronunciation issues in English.